2x²+(-x²-2xy+2y²)-2(x²-xy+2y²)其中x=-1 y=2分之1

来源:学生作业帮助网 编辑:六六作业网 时间:2024/07/10 17:57:21
2x²+(-x²-2xy+2y²)-2(x²-xy+2y²)其中x=-1y=2分之12x²+(-x²-2xy+2y²)-

2x²+(-x²-2xy+2y²)-2(x²-xy+2y²)其中x=-1 y=2分之1
2x²+(-x²-2xy+2y²)-2(x²-xy+2y²)其中x=-1 y=2分之1

2x²+(-x²-2xy+2y²)-2(x²-xy+2y²)其中x=-1 y=2分之1
2x²+(-x²-2xy+2y²)-2(x²-xy+2y²)
=2x²-x²-2xy+2y²-2x²+2xy-4y²
=2x²-x²-2x²+2xy-2xy+2y²-4y²
=-x²-2y²
=-(-1)²-2*(1/2)²
=-1-2*1/4
=-1-1/2
=-3/2

2x²+(-x²-2xy+2y²)-2(x²-xy+2y²)
=2x²-2xy+2y²
-x²+2xy-4y²
-2x²
=-x²-2y²
x=-1 y=2分之1
-x²-2y²
=-1-1/2
=-3/2